2008
DOI: 10.1007/s11947-008-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Some Physico-chemical, Thermal, Morphological, and Pasting Properties of Acid-thinned Jicama and Maize Starches

Abstract: Comparative studies on acid hydrolysis of jicama and maize starch were carried out using concentrations of hydrochloric acid of 1.5%, 3.0%, and 4.5% (w/v), for 3 and 6 h, at 40°C. Native maize and jicama starches showed important morphological, thermal, and structural differences from those of tubers and cereals which potentially offer diverse industrial applications. Jicama starch showed low amylose content (12%) and small size of starch granules. Due to these characteristics, jicama starch was more susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 40 publications
(53 reference statements)
5
21
0
Order By: Relevance
“…Consistent with the results of present study, an increase in S by acid treatment has been reported in the literature for the starches of corn (normal and waxy), cassava, jicama, potato, rice, sago, and sorghum .…”
Section: Resultssupporting
confidence: 93%
“…Consistent with the results of present study, an increase in S by acid treatment has been reported in the literature for the starches of corn (normal and waxy), cassava, jicama, potato, rice, sago, and sorghum .…”
Section: Resultssupporting
confidence: 93%
“…For practical use, starch generally undergoes mild acid‐hydrolysis to obtain acid‐thinned starch with a targeted viscosity. Compared with that of the control starch, the gelatinization properties of acid‐thinned starch do not show a clear trend of changes (Table ) , which is attributed to different hydrolysis conditions (e.g., acid concentration, incubation temperature and time) and various types of starch used in the studies.…”
Section: Gelatinization Property Of Starchmentioning
confidence: 92%
“…[35] The differences in pasting properties of corn varieties are also reported in literature. [6,26,36] Textural properties of starch gel…”
Section: X-ray Diffractionmentioning
confidence: 99%